2005
DOI: 10.1016/j.envint.2005.05.041
|View full text |Cite
|
Sign up to set email alerts
|

Yield and arsenate uptake of arbuscular mycorrhizal tomato colonized by Glomus mosseae BEG167 in As spiked soil under glasshouse conditions

Abstract: A glasshouse pot experiment was conducted to study the effect of arbuscular mycorrhizal (AM) colonization by Glomus mosseae BEG167 on the yield and arsenate uptake of tomato plants in soil experimentally contaminated with five As levels (0, 25, 50, 75 and 150 mg kg À 1 ). Mycorrhizal colonization (50 -70% of root length) was little affected by As application and declined only in soil amended with 150 mg As kg À 1 . Mycorrhizal colonization increased plant biomass at As application rates of 25, 50 and 75 mg kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
37
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 29 publications
6
37
1
Order By: Relevance
“…However, the As concentration that affected this fungus colonization was markedly lower than that previously observed to affect Glomus mosseae growth in soil [29,30]. Gildon and Tinker [31] found that the occurrence of toxic elements in the soil can inhibit mycorrhizal colonization, but Smith et al [10] established that the presence of As does not reduce the percentage of root colonization.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…However, the As concentration that affected this fungus colonization was markedly lower than that previously observed to affect Glomus mosseae growth in soil [29,30]. Gildon and Tinker [31] found that the occurrence of toxic elements in the soil can inhibit mycorrhizal colonization, but Smith et al [10] established that the presence of As does not reduce the percentage of root colonization.…”
Section: Resultsmentioning
confidence: 80%
“…However, mycorrhizae altered this relation since AM fungi inoculation reduced to one third the As accumulated in roots, as well as the As accumulated in leaves (although less markedly). Other authors have recorded lower As concentrations on mycorrhized plants such as maize [29], tomato [31], lentil [35], clover [36], sunflower [37], rye grass and white clover [38], and plants growing on As-contaminated areas [26]. They have stated different hypotheses: (i) mycorrhizal inoculation improves the plant yield and causes a dilution effect in the As concentration; (ii) AM fungi hyphae exhibit a great variety of free groups such as hydroxyl, carboxyl, and amino acids, which could bind to As, retaining it in the fungal tissues and reducing the As intake by roots.…”
Section: Resultsmentioning
confidence: 99%
“…Their capacity to enhance the tolerance of host plants to As contamination in soil has been addressed (7,8). AM fungi have also been reported to reduce plant uptake of As such as by the fern Pteris vittata L (9), lentil (10), alfalfa (11), tomato (12), and sunflower (13). Considering the interactions between AM fungi with soil microorganisms in the rhizosphere and their influence on plant uptake of nutrition such as P, we speculated that AM fungi might influence As speciation in soil and plant growth in As contaminated soil.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, AMmycorrhized plants often show an enhanced metal(loid) tolerance (Garg and Bhandari, 2014;G€ ohre and Paszkowski, 2006, and references therein). However, the role of these fungi in the plant uptake and translocation of Cd is not clear, as it is influenced by many factors (Garg and Bhandari, 2014;Janou skov a et al, 2005), and there are few data on As, particularly as regards nonhyperaccumulator plants (Hua et al, 2009;Liu et al, 2005). In the As-hyperaccumulator fern Pteris vittata, hosting the AM symbiosis with Glomus mosseae (now renamed Funneliformis mosseae, see the M&M subsection 2.1.…”
Section: Introductionmentioning
confidence: 99%